The Benefit of Professional Education on the Performance of Civil Servants - Vorel, David; Válek, Jan; Sládek, Petr; Šibor, Jiří (R&E-SOURCE, 2023)
The paper is devoted to the benefit of professional education to employees’ work performance. A properly set up education system motivates employees to continue their education and subsequently facilitates their work activities. However, simply completing a properly planned training course may not guarantee the facilitation of the performance of work activities. By subsequent evaluation of the educational activities of the employees, it is necessary to find out whether the setting of professional education is beneficial for them or not. The education system needs to be looked at holistically. It is impossible to separate the benefit for the employees and the knowledge gained by completing the course. Therefore, it is necessary to focus on the effectiveness of professional education to determine knowledge at the input and output of educational courses. The research was based on findings from groups of civil servants.